2008
DOI: 10.1111/j.1600-0722.2008.00543.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori in human oral cavity and stomach

Abstract: The oral cavity has been suspected as an extra-gastroduodenal reservoir for Helicobacter pylori infection and transmission, but conflicting evidence exists regarding the occurrence of H. pylori in the mouth, independently of stomach colonization. Ninety-four gastric biopsy patients were analysed for the concurrent presence of H. pylori in the mouth and stomach. Samples were collected from different areas within the mouth and H. pylori DNA was amplified by the polymerase chain reaction (PCR) and verified by seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 43 publications
3
51
1
3
Order By: Relevance
“…Varios estudios han demostrado la presencia de H. pylori simultáneamente en cavidad oral y mucosa gástrica, mostrando diferentes prevalencias, dependiendo de la población estudiada, la selección de la muestra y técnicas de detección de la bacteria [26][27][28][29][30][31][32][33]40 . Mapstone 41 , demostró que la presencia de H. pylori en la boca de pacientes dispépticos es importante para su diseminación y considera la cavidad oral una potencial fuente de reinfección luego de la erradicación del microorganismo del estómago.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Varios estudios han demostrado la presencia de H. pylori simultáneamente en cavidad oral y mucosa gástrica, mostrando diferentes prevalencias, dependiendo de la población estudiada, la selección de la muestra y técnicas de detección de la bacteria [26][27][28][29][30][31][32][33]40 . Mapstone 41 , demostró que la presencia de H. pylori en la boca de pacientes dispépticos es importante para su diseminación y considera la cavidad oral una potencial fuente de reinfección luego de la erradicación del microorganismo del estómago.…”
Section: Discussionunclassified
“…Algunos autores han encontrado una asociación entre la presencia de H. pylori en mucosa gástrica y oral [26][27][28][29][30][31][32][33] . En una investigación previa realizada por nuestro grupo, se observó la co-existencia de la bacteria en ambas localizaciones mediante RPC en tiempo real (RPC-TR) 34 .…”
Section: +16unclassified
“…However based on some evidence oral cavity can be considered a reservoir for H. pylori in non-dyspeptic individuals, some researchers believe in temporary presence of H. pylori in such situation (Martinez-Gomis et al, 2006;Burgers et al, 2008). Other researchers believe that non-infectious H. pylori might exist in the oral cavity which is just able to form colonies and invade tissues under special conditions such as concomitant infections (Martinez-Gomis et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Identical strains have been found in gastric mucosa and oral cavity. The first comparison of gastric and oral H. pylori strains using PCR genotyping performed Wang et al (2002) and, consequently, Burgers et al (2008). Different genotypes in the stomach and oral cavity were found in both studies.…”
Section: Comparison Of Oral and Oropharyngeal Genotypesmentioning
confidence: 99%
“…Different genotypes in the stomach and oral cavity were found in both studies. PCR assays used by these authors could be considered more accurate Burgers et al (2008), who report that only 38% of persons with demonstrated presence of H. pylori in the oral cavity also had the infection in the stomach. These authors also reported the finding of 10 cases with positive H. pylori in saliva, with no detectable specific anti-H. pylori antibodies in serum.…”
Section: Comparison Of Oral and Oropharyngeal Genotypesmentioning
confidence: 99%